Pembelajaran Sastra Berbasis Karya Sastra yang Bersumber dari Majalah Suara 'Aisyiyah - Firdaus, Asep; Suparman, Fauziah (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to determine the use of teaching materials for literary works sourced from Suara 'Aisyiyah magazine. The method used in this research is a qualitative research method with descriptive analysis techniques. This research describes the suitability of implementing poetry sourced from the magazine Suara ‘Aisyiyah to be used as teaching material in literature learning at Muhammadiyah High School, Sukabumi City. The results of the analysis show that the poems taken and used in literature learning at the Muhammadiyah High School in Sukabumi City, namely the poems "Soundless Screams" and "The Owner of Earth" by Cheny Kurata A'Yun, can be used as suitable teaching materials for students, especially in studying material about the building blocks of a poem at the high school level. Keyword: learning literature, poetry and Aisyiah magazines